2005
DOI: 10.1111/j.1365-277x.2004.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Usual diet in Bubis, a rural immigrant population of African origin in Madrid

Abstract: The first immigrant generation of Bubis in Madrid showed food and nutrient intakes closer to the prevalent diet in Madrid than to the diet of their native land. The impact of this westernization of the diet of this and other immigrant populations in Spain needs to be monitored in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 14 publications
3
27
0
4
Order By: Relevance
“…Among the Bubis in Madrid, two dietary patterns were identified. Most participants adhered to the ‘healthier’ pattern, which was associated with a higher consumption of fish, fruits, vegetables, legumes, dairy products and bread [16]. Similar to the ‘mixed’ patterns in the present study, the ‘healthier’ pattern among Bubis was strongly related to female sex, longer duration of residence in Spain, and former smoking.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Among the Bubis in Madrid, two dietary patterns were identified. Most participants adhered to the ‘healthier’ pattern, which was associated with a higher consumption of fish, fruits, vegetables, legumes, dairy products and bread [16]. Similar to the ‘mixed’ patterns in the present study, the ‘healthier’ pattern among Bubis was strongly related to female sex, longer duration of residence in Spain, and former smoking.…”
Section: Discussionsupporting
confidence: 73%
“…Something similar was observed in a study among 213 migrants from Equatorial Guinea (Bubis) living in Madrid; the diet was richer in protein intake and lower in fat than the original Guinean diet [16]. Among the Bubis in Madrid, two dietary patterns were identified.…”
Section: Discussionsupporting
confidence: 67%
“…Dairy products, meat, fish, raw vegetables, and fruits were eaten on a daily basis, while eggs, potatoes, and pulses were eaten weekly. 24 Likewise, Montoya et al 25 reported that first-and second-generation immigrants (n = 356), aged 6-12 years living in Madrid, consumed more fruits, vegetables, legumes, and eggs but less fish and dairy products than the indigenous Spaniards, suggesting that the young immigrants had healthier diets.…”
Section: Importance Of Ethnic Groupsmentioning
confidence: 99%
“…Traditional starchy vegetables were reported to be consumed up to three times a month in this population. Dairy products, meat, fish, raw vegetables, and fruits were eaten on a daily basis, while eggs, potatoes, and pulses were eaten weekly 24 . Likewise, Montoya et al 25 .…”
Section: Dietary Habits and Eating Patternsmentioning
confidence: 99%
“…The same study found that children of Asian and Middle‐Eastern cultural background spent more time per week than their English‐speaking background counterparts engaged in sedentary behaviours. Other studies in countries, such as the United States and Spain, have reported that immigrants of African origin fare the worst [16], [23–27].…”
Section: Introductionmentioning
confidence: 91%